2017
DOI: 10.3168/jds.2016-11913
|View full text |Cite
|
Sign up to set email alerts
|

The effects of heat stress on protein metabolism in lactating Holstein cows

Abstract: Heat stress (HS) decreases milk protein synthesis beyond what would be expected based on the concomitant reduction in feed intake. The aim of the present study was to evaluate the direct effects of HS on milk protein production. Four multiparous, lactating Holstein cows (101 ± 10 d in milk, 574 ± 36 kg of body weight, 38 ± 2 kg of milk/d) were individually housed in environmental chambers and randomly allocated to 1 of 2 groups in a crossover design. The study was divided into 2 periods with 2 identical experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
123
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(171 citation statements)
references
References 36 publications
23
123
2
3
Order By: Relevance
“…Nutrition appears to have little effect on the synthesis of the major milk proteins by mammary secretory cells (MacRae et al, 2000). On the other hand, heat stress was shown to increase systemic AA utilization, which limits the AA supply to the mammary gland for the synthesis of milk proteins (Gao et al, 2017).…”
Section: Genetic and Environmental Relationships Between Bhb And Uddementioning
confidence: 99%
“…Nutrition appears to have little effect on the synthesis of the major milk proteins by mammary secretory cells (MacRae et al, 2000). On the other hand, heat stress was shown to increase systemic AA utilization, which limits the AA supply to the mammary gland for the synthesis of milk proteins (Gao et al, 2017).…”
Section: Genetic and Environmental Relationships Between Bhb And Uddementioning
confidence: 99%
“…Prolactin is not only a hormone related to milk production, but has a broad variety of biological functions related to thermoregulation and water balance. The increase in plasma prolactin is not reflected in an increase in milk yield, as seen in dairy ruminants under HS conditions [11, 43]. Alamer [44] concluded that the mammary gland experiences a down-regulation of prolactin signaling pathways that could partially explain the depressed milk production of dairy cows during HS.…”
Section: Resultsmentioning
confidence: 99%
“…sowie Energie-und Proteinstoffwechsel (7)(8)(9) Endokrinologische Prozesse (8,20,24) Entwicklung von Embryo/Fetus/Kalb (intrauterin/post natum) (26)(27)(28)(29)(30) Verhalten (13,14) Elektrolyt-und Säure-Basen-Haushalt (15)(16)(17) Physiologische Parameter (Atem-/Herzfrequenz, Rektaltemperatur) (18)(19)(20) Inflammatorische und immunologische Prozesse (38)(39)(40) Oxidativer Stress (34,35) Fruchtbarkeit/ Reproduktionsleistung klimatischen Bedingungen während der Laktation, sondern auch jene während der vorherigen Trockenstehzeit [10]. Darüber hinaus gibt es Hinweise, dass Hitzestress bei tragenden Kühen die spätere Milchleistung der aus diesen Trächtigkeiten hervorgegangenen Färsen -möglicherweise über epigenetische Mechanismen vermittelt -nachteilig beeinflusst [11] [12].…”
Section: Nährstoffverdaulichkeitunclassified
“…Ergebnisse Trotz der bereits zu Beginn des Beobachtungszeitraumes recht hohen Außentemperaturen (19,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23),0° C im Tagesmittel) traten während einer Hitzeperiode (bis zu 27,9° C im Tagesmittel) deutliche Reduktionen in der Trockensubstanzaufnahme aus der Teil-TMR (ca. -15 %) und der Milchleistung (ca.…”
unclassified